Bacterial microbiota of three commercially mass-reared predatory mite species (Mesostigmata: Phytoseiidae): pathogenic and beneficial interactions - Sumner-Kalkun, Jason C.; Baxter, Ian; Perotti, M. Alejandra (Frontiers in Arachnid Science, 2023)
Phytoseiidae predatory mites are used as biological control agents in glasshouse environments to control pestiferous mites and insects.. The influence of the microbiomes on these mites within mass reared facilities is largely unknown; this study aims to improve our understanding of the Phytoseiidae microbiome. We used Sanger sequencing and traditional culturing methods to characterise the dominant species within the external and internal bacterial microbiotas of three commercially reared predatory mites: Phytoseiulus persimilis, Typhlodromips (=Amblysieus) swirskii, and Neoseiulus (=Amblyseius) cucumeris. The effects of selected bacterial taxa on the survival, voracity, and oviposition of P. persimilis under lab conditions were also examined. 34 different OTUs were found from 3 phyla (Actinobacteria, Proteobacteria and Firmicutes), 12 families and 22 genera. N. cucumeris had 17 OTUs, compared to 15 from P. persimilis and 12 from T. swirskii. Significant differences were found between internal and external microbiota for each mite species suggesting functional differences. Principal component analysis (PCA) of bacterial diversity between mite species showed that Typhlodromips swirkii and Neoseiulus cucumeris microbiotas were more similar, compared to Phytoseiulus persimilis. This could be due to the characteristics of the environment in which N. cucumeris and T. swirskii are reared, and the use of factitious Astigmata prey. Phytoseiidae microbiotas were found to contain bacterial taxa previously isolated from Astigmata mites. Also, Acaricomes phytoseiuli was isolated from the integument of P. persimilis and T. swirskii, this bacterium has previously been suggested as a pathogen of P. persimilis. Bacteria from gut extracts and body surfaces were cultured and selected taxa were inoculated onto P. persimilis within controlled leaf disc experiments. Of the seven bacterial species tested, Serratia marcescens significantly reduced mite survival, voracity, and oviposition; however, a closely related species Serratia odorifera significantly increased mite voracity. Mites showed the highest survival rates and highest mean ages at death in the presence of Elizabethkingia sp. and Staphylococcus kloosii, but these results were not significantly different to the control. The implications of these findings are discussed in the context of benefits to mass rearing and the health of predatory mites in these systems.